THE USE OF INTERACTIVE METHODS IN TEACHING FOREIGN LANGUAGES (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the role of interactive methods in foreign language teaching, emphasizing their effectiveness in promoting active learning, enhancing language skills, and fostering student engagement. It explores the evolution of language teaching methods, focusing on the transition from traditional teacher-centered approaches to more communicative, student-centered practices. Key theories such as Communicative Language Teaching (CLT), Task-Based Learning (TBL), and collaborative learning are discussed, highlighting their impact on language acquisition. The article presents various interactive methods, including group work, role-plays, and project-based tasks, and their application in the classroom. Through literature review and practical examples, the study shows that interactive methods improve students’ speaking, listening, and intercultural communication skills while boosting motivation and learner autonomy. However, challenges like classroom management, time constraints, and technology integration are also addressed. The article concludes that while interactive methods offer substantial benefits, their successful implementation requires careful planning and adaptation to diverse teaching contexts.
Keywords: Interactive methods, foreign language teaching, task-based learning, communicative language teaching, group work, student motivation, classroom management, technology integration.